(untitled) (Global Business Management Review (GBMR), 2022)
There is no doubt that a resource crucial for the continued growth and survival of a company is capital. As a company’s investment scale increases, the need for additional capital becomes paramount. One way by which a company raises capital is through initial public offerings (IPOs). However, the amount of capital raised in the IPO market varies among companies. It is on this note that this study aimed to examine the factors that affect the amount of capital a company can raise during an IPO activity. To achieve the aim of this study, data was collected from pre-IPO prospectuses of the sampled IPOs. The study made particular reference to the signalling, upper echelons and resource dependence theories to identify the pre-IPO characteristics that could influence the amount of capital a company can raise in the IPO market. The results from this study provide valuable information that could help issuers to identify appropriate mechanisms that would signal the company’s quality and influence the value of the company. The results also provide hints to prospective investors on the managerial characteristics and company-specific characteristics to be considered when making investment decisions. The implication is that IPO issuers should pay attention to such criteria when making IPO decisions in order to maximize the value from the offerings. The results would also be important to several interested groups when a company undertakes an IPO decision.